2017
DOI: 10.1111/hdi.12531
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of intradialysis calcium mass balance by a single pool variable‐volume calcium kinetic model

Abstract: Introduction: A reliable method of intradialysis calcium mass balance quantification is far from been established. We herein investigated the use of a single-pool variable-volume Calcium kinetic model to assess calcium mass balance in chronic and stable dialysis patients.Methods: Thirty-four patients on thrice-weekly HD were studied during 240 dialysis sessions. All patients were dialyzed with a nominal total calcium concentration of 1.50 mmol/L. The main assumption of the model is that the calcium distributio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 19 publications
1
24
0
Order By: Relevance
“…However, in different studies, both a positive and negative DCa were observed during a DCa of 3.0 mEq/L [34,35]. Other studies have showed that the use of a DCa of 2.5 mEq/L had in general a neutral effect on SCa levels, but with variable effects on CaMB [36].…”
Section: Camb In Hemodialysismentioning
confidence: 91%
See 2 more Smart Citations
“…However, in different studies, both a positive and negative DCa were observed during a DCa of 3.0 mEq/L [34,35]. Other studies have showed that the use of a DCa of 2.5 mEq/L had in general a neutral effect on SCa levels, but with variable effects on CaMB [36].…”
Section: Camb In Hemodialysismentioning
confidence: 91%
“…In the context of the DialysIS study, a more rigorous method capable of quantifying the intradialytic CaMB was proposed [35]. The proposed single-pool variablevolume kinetic model, tested in patients treated with a DCa concentration of either 3.0 or 3.5 mEq/L took into account all aspects of diffusive and convective exchange using bicarbonate dialysis.…”
Section: Camb In Hemodialysismentioning
confidence: 99%
See 1 more Smart Citation
“…calcium, potassium and phosphorus, that play a crucial role for hydro-electrolyte equilibria. [16][17][18] To achieve more effective prediction models, multi-pool models have been introduced, allowing to describe the simultaneous contribution of different plasma solutes. 19 However, none of these models aim at characterizing the patientspecific solute kinetics in HD, apart from Ursino et al, 19 in which an individual estimation of few parameters characterizing solute kinetics has been performed.…”
Section: Dialysis Modelingmentioning
confidence: 99%
“…This fact is proved by the presence of kinetic models specific for calcium. 16 We now consider the LFO case. The marginal posterior densities of the patient-specific parameters for these tests, compared with the true values used to generate the simulated datasets, are reported in Tables 4-6.…”
Section: à4mentioning
confidence: 99%